Multifunctional composite material for mineralizing and storing CO2 based on fly ash and preparation method of multifunctional composite material

By performing plasma activation treatment on fly ash, combined with nano-scale metal oxide catalysts and metal organic framework functionalized organic ligands, using intelligent pH regulators and ultrasonic enhancement technology, the problems of low CO2 storage efficiency and difficulty in resource utilization of fly ash are solved, and efficient CO2 storage and high value-added utilization of fly ash are achieved.

CN119819268AActive Publication Date: 2025-04-15CHINA UNIV OF MINING & TECH +2

Patent Information

Application Number
CN202510042102.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The existing CO2 storage technology has challenges in terms of economics and sustainability, especially in low storage efficiency, expensive cost and insufficient long-term stability. At the same time, there is room for improvement in the resource utilization of industrial by-product fly ash.

Method used

The multifunctional composite material based on fly ash mineralization and sealing CO2 is used to treat fly ash through plasma activation, combined with nano-scale metal oxide catalyst and metal organic framework functionalized organic ligand ZIF-8 MOF, combined with intelligent pH regulator and ultrasonic enhancement technology, efficient mineralization reaction and product separation are carried out.

Benefits of technology

It significantly improves the storage efficiency of CO2, generates stable carbonate products, realizes high value-added utilization of fly ash, reduces carbon emissions and improves the utilization rate of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819268A_ABST
    Figure CN119819268A_ABST
Patent Text Reader

Abstract

The invention discloses a multifunctional composite material for mineralizing and storing CO2 based on fly ash and a preparation method of the multifunctional composite material. The material is prepared from high-activity fly ash subjected to plasma activation treatment, a nanoscale metal oxide catalyst, a metal organic framework, a functional organic ligand, an intelligent pH regulator, a solid suspension stabilizer and water. The preparation method comprises the steps of suspension preparation, high-pressure CO2 mineralization reaction in a reaction kettle, centrifugal separation and freeze drying treatment. The method is simple, the raw material cost is low, the prepared multifunctional composite material not only can remarkably improve the storage efficiency of CO2, but also can ensure that a stable carbonate product is generated, and the carbonate product has high specific surface area and excellent chemical stability, can be widely applied to the fields of high-end building materials, energy storage materials and fine chemical engineering, and has wide application prospects. And meanwhile, the high-added-value utilization of the industrial by-product fly ash is realized, and the dual purposes of reducing carbon emission and improving the utilization rate of solid wastes are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon dioxide capture and storage (CCS), and in particular to a multifunctional composite material for CO2 storage based on fly ash mineralization and a preparation method thereof, and belongs to the intersecting field of environmental engineering, solid waste resource utilization and green and low-carbon technology. Background Art

[0002] As the global climate change problem becomes increasingly serious, carbon dioxide (CO2), as one of the main greenhouse gases, has an increasingly negative impact on the environment. In order to effectively reduce CO2 emissions, carbon dioxide capture and storage (CCS) technology has gradually become one of the important strategies for addressing climate change worldwide. However, existing CO2 storage technologies face many challenges in terms of economy and sustainability, especially low storage efficiency, high cost, and insufficient long-term stability. In addition, with the rapid development of global industrialization, the emission of industrial by-products such as fly ash has increased year by year. How to efficiently and environmentally friendlyly utilize these wastes has become an important issue that needs to be urgently addressed in the industrial and environmental protection fields.

[0003] Fly ash is the main waste product of coal-fired power plants. It contains rich silicon, aluminum, active calcium oxide and other components, and has the potential to undergo mineralization reactions with CO2. Fly ash mineralization and CO2 storage can not only effectively reduce greenhouse gas emissions, but also achieve resource recycling of solid waste. However, there is still much room for improvement in the traditional fly ash mineralization CO2 technology in terms of reaction efficiency and product stability. In order to improve the storage efficiency of CO2, accelerate the reaction rate, and enhance the stability and added value of the product, it is imperative to study more efficient catalysts, multifunctional auxiliary materials and innovative mineralization reaction processes. Summary of the invention

[0004] The purpose of the present invention is to provide a multifunctional composite material for CO2 storage based on fly ash mineralization and a preparation method thereof. The method is simple and has low raw material cost. The prepared multifunctional composite material can not only significantly improve the CO2 storage efficiency, but also ensure the generation of stable carbonate products, while realizing the high added value utilization of fly ash, an industrial by-product, to achieve the dual goals of reducing carbon emissions and improving the utilization rate of solid waste.

[0005] To achieve the above object, the present invention provides a multifunctional composite material for CO2 storage based on fly ash mineralization, which is composed of the following raw materials in parts by weight: 70-85 parts of fly ash treated with plasma activation, 3-7 parts of nano-scale metal oxide catalyst, 5-10 parts of metal organic framework functionalized organic ligand ZIF-8 type MOF, 1-2 parts of intelligent pH regulator poly (acrylic acid-co-acrylamide) copolymer, 3-5 parts of solid suspension stabilizer, and 10-20 parts of high-purity water;

[0006] The fly ash treated by plasma activation contains 50-65wt% SiO2, 20-30wt% Al2O3 and 5-15wt% CaO;

[0007] The preparation process of the nano-scale metal oxide catalyst is as follows: calcium oxide, magnesium oxide and zinc oxide are weighed in order according to the ratio, ball-milled and mixed to obtain a mixed powder, calcined at high temperature to form a composite oxide, and then the composite oxide is placed in a graphene dispersion liquid, ultrasonically dispersed, and the graphene is uniformly coated on the surface of the composite oxide to obtain the nano-scale metal oxide catalyst;

[0008] The solid suspension stabilizer is polyvinyl alcohol or modified polyvinyl pyrrolidone.

[0009] Furthermore, the treatment process of the fly ash treated with plasma activation is: collecting fly ash in a dust-free environment, screening to remove large impurities, putting it into a plasma reactor, introducing oxygen, the oxygen flow rate is 10-50L / min, adjusting the plasma generator power to 500-1500W, treating at 800-1200°C for 1-2h, and naturally cooling to room temperature.

[0010] Furthermore, the preparation process of the metal organic framework functionalized organic ligand ZIF-8 type MOF is as follows: accurately weigh zinc nitrate as a metal salt and 2-methylimidazole as an organic ligand and put them into a reaction bottle, the molar ratio between zinc ions and 2-methylimidazole is 1:2, deionized water is added to adjust the pH to 3-6, and a hydrothermal synthesis reaction is carried out at 80-120°C in a constant temperature water bath for 12-48 hours. After the reaction is completed, it is naturally cooled, centrifuged to obtain a MOF material, and the MOF material is washed with anhydrous ethanol for 3-5 times and vacuum dried at 60-80°C for 12-24 hours.

[0011] Preferably, the molar ratio of calcium oxide, magnesium oxide and zinc oxide is 1: (0.5-1.5): (0.3-1); ball milling mixing is 2-4h; calcination temperature is 800-900°C, and calcination time is 2-4h; ultrasonic dispersion is 1-3h; and the concentration of graphene dispersion is 5-15mg / mL.

[0012] Preferably, the mass ratio of acrylic acid to acrylamide in the poly(acrylic acid-co-acrylamide) copolymer is 1:(0.8-1.2), and the molecular weight of the poly(acrylic acid-co-acrylamide) copolymer is 50,000-100,000.

[0013] Preferably, the molecular weight of the polyvinyl alcohol is 100,000-300,000; the modification process of the modified polyvinyl pyrrolidone is as follows: divinyl benzene is used as a crosslinking agent, and a chemical crosslinking reaction occurs with polyvinyl pyrrolidone under the action of an initiator, and the crosslinking degree is controlled at 5%-15%.

[0014] To achieve the above object, the present invention also provides a method for preparing the above multifunctional composite material based on fly ash mineralization and CO2 storage, comprising the following steps:

[0015] S1. Mix fly ash treated with plasma activation, nano-scale metal oxide catalyst, metal organic framework functionalized organic ligand ZIF-8 type MOF and high-purity water in proportion, add solid suspension stabilizer during stirring, stir evenly to form a suspension, and stir for 30-60 minutes;

[0016] S2. Place the suspension in a high-pressure reactor, control the reaction temperature to 40-80°C and the pressure to 5-10MPa, introduce CO2 gas under ultrasonic conditions, and carry out mineralization reaction for 2-6 hours; during the mineralization process, use the intelligent pH regulator poly(acrylic acid-co-acrylamide) copolymer to dynamically control the pH value of the reaction environment to 7-9;

[0017] S3. Centrifuge the reaction solution obtained in step S2 at a speed of 3000-5000 rpm for 30-60 min to separate the mineralized product from the suspension by high-speed centrifugation, and then place the precipitate in a freeze dryer and dry it at -40°C to -20°C for 12-24h to obtain an ultrafine nano-scale carbonate solid material, i.e., a multifunctional composite material.

[0018] Preferably, in step S2, graded temperature control is adopted, the reaction temperature is controlled at 60-80°C in the initial stage of the reaction, and the reaction is carried out for 1-3 hours; then the temperature is lowered to 40-50°C and the reaction is carried out for 1-3 hours.

[0019] Furthermore, in step S2, a poly(acrylic acid-co-acrylamide) copolymer aqueous solution with a mass concentration of 5%-10% is pre-prepared as an intelligent pH regulator, and the intelligent pH regulator is added before the suspension is added to the high-pressure reactor.

[0020] Preferably, in step S2, the ultrasonic oscillation frequency is 20-40kHz; the CO2 gas flow rate is 10-50mL / min.

[0021] Compared with the prior art, the composite material prepared by the present invention has the following advantages:

[0022] (1) Highly efficient CO2 capture and mineralization capabilities: The nanoscale metal oxide catalyst in the present invention can improve the conductivity and surface activity of the catalyst, thereby significantly improving the CO2 mineralization efficiency; the metal organic framework functionalized organic ligand adopts a metal organic framework (MOF) material with a three-dimensional porous structure to enhance its adsorption capacity and selectivity for CO2 molecules; the present invention significantly improves the CO2 capture capacity and mineralization reaction rate through the synergistic effect of the nanoscale metal oxide catalyst and the metal organic framework functionalized organic ligand, thereby achieving efficient CO2 storage.

[0023] (2) Excellent chemical stability: The mineralization product of the present invention is nano-scale carbonate particles, the main components of which are calcium carbonate and magnesium carbonate, with a purity of not less than 95% and a particle size range of 10-100 nanometers. It has high crystallinity, high specific surface area and excellent chemical stability, and can withstand a wide range of temperature changes and acid-base environments. It is suitable for high-end building materials, energy storage materials and environmental remediation fields.

[0024] (3) Green and environmentally friendly: The present invention utilizes fly ash, an industrial by-product, as the main raw material, thus realizing the resource utilization of waste and reducing environmental pollution and resource waste.

[0025] Compared with the prior art, the preparation method of the present invention has the following advantages:

[0026] (1) Plasma activation treatment: The fly ash of the present invention is treated with high-temperature plasma to enhance the surface activity of the fly ash and improve its reactivity with CO2, thereby optimizing the mineralization reaction kinetics;

[0027] (2) Ultrasonic enhancement technology: The present invention uses ultrasonic oscillation during the mineralization reaction to improve the contact efficiency between CO2 and fly ash particles, further accelerating the mineralization reaction;

[0028] (3) Graded temperature control strategy: The present invention adopts a graded temperature control strategy during the mineralization reaction, maintaining a relatively high temperature in the early stage of the reaction to accelerate CO2 absorption, and cooling in the later stage to ensure high purity and crystal integrity of the mineralized product;

[0029] (4) Intelligent pH adjustment technology: The intelligent pH adjuster in the present invention is a polymer material poly(acrylic acid-co-acrylamide) copolymer with adaptive response capability. The adjuster can dynamically adjust the solution pH to the optimal range according to the change of CO2 concentration during the reaction process, thereby ensuring reaction stability and optimal mineralization conditions and maximizing mineralization efficiency;

[0030] (5) High-efficiency separation and drying technology: The present invention adopts high-speed centrifugal separation technology and freeze-drying technology to effectively separate the mineralized products, retain the structure and chemical properties of the products, and improve the stability of the mineralized products.

[0031] In summary, the present invention significantly improves the capture and mineralization efficiency of carbon dioxide (CO2) and the storage efficiency of CO2 by introducing nano-scale metal oxide catalysts, metal organic framework functionalized organic complexes, plasma activation treatment, ultrasonic enhancement technology and intelligent control technology, and meets the requirements of industrial application; optimizes the reaction conditions, generates high value-added stable carbonate products, and further realizes the resource utilization of industrial by-product fly ash, achieving the dual goals of reducing carbon emissions and improving the utilization rate of solid waste. The present invention has the characteristics of high efficiency, green environmental protection, simple preparation method, low material cost, and significantly improved storage efficiency, and is suitable for large-scale industrial application in carbon capture and storage (CCS) technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A comparison chart of mechanical properties between the multifunctional composite material prepared by the present invention and common building materials;

[0033] Figure 2 It is the adsorption-desorption isotherm diagram of the multifunctional composite material prepared by the present invention. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0035] Example 1

[0036] A multifunctional composite material for CO2 storage based on fly ash mineralization, comprising the following raw materials in parts by weight: 80 parts of fly ash treated with plasma activation, 5 parts of nano-scale metal oxide catalyst, 8 parts of metal organic framework functionalized organic ligand ZIF-8 type MOF, 1.5 parts of intelligent pH regulator poly (acrylic acid-co-acrylamide) copolymer, 4 parts of solid suspension stabilizer, and 15 parts of high-purity water;

[0037] The fly ash treated by plasma activation contains 60wt% SiO2, 25wt% Al2O3, 10wt% CaO and 5wt% unavoidable impurities;

[0038] The fly ash is treated with high-temperature plasma to improve its surface activity and reactivity. During the treatment process, oxygen plasma reacts with metal oxides in the fly ash, increasing the specific surface area of ​​the fly ash, thereby improving its reactivity with CO2. The specific treatment process is as follows: collect the fly ash in a dust-free environment, screen and remove large impurities, put it into a plasma reactor, introduce oxygen, set the oxygen flow rate to 30L / min, and adjust the plasma generator power to 1000W to ensure that the fly ash surface can fully contact the plasma; treat at 1000℃ for 1.5h to ensure the maximization of the surface activity of the fly ash; after the treatment is completed, take out the fly ash and cool it naturally to room temperature for use.

[0039] The preparation process of the nano-scale metal oxide catalyst is as follows: calcium oxide, magnesium oxide and zinc oxide are first put into a ball mill at a molar ratio of 1:1:0.5, mixed and ball-milled for 3 hours to obtain a mixed powder, the mixed powder is calcined at 850° C. for 3 hours under nitrogen protection to obtain a composite oxide, and the composite oxide is naturally cooled to room temperature and then placed in a graphene dispersion liquid with a concentration of 10 mg / mL, ultrasonically dispersed for 2 hours to uniformly coat the graphene on the surface of the composite oxide, and uncoated graphene is separated by centrifugation to obtain a nano-scale metal oxide catalyst;

[0040] The preparation process of the metal organic framework functionalized organic ligand ZIF-8 type MOF is as follows: accurately weigh zinc nitrate as a metal salt and 2-methylimidazole as an organic ligand and put them into a reaction bottle, the molar ratio between zinc ion and 2-methylimidazole is 1:2, add deionized water to adjust the pH to 4.5, perform hydrothermal synthesis reaction at 100° C. in a constant temperature water bath for 24 hours, cool naturally after the reaction is completed, centrifuge to obtain MOF material, wash the MOF material with anhydrous ethanol 4 times and vacuum dry it at 70° C. for 18 hours;

[0041] The mass ratio between acrylic acid and acrylamide in the smart pH regulator poly(acrylic acid-co-acrylamide) copolymer is 1:1, and the molecular weight of the poly(acrylic acid-co-acrylamide) copolymer is 80,000;

[0042] The solid suspension stabilizer is polyvinyl alcohol, and the molecular weight of the polyvinyl alcohol is 200,000.

[0043] The preparation method of the above-mentioned multifunctional composite material for CO2 storage based on fly ash mineralization comprises the following steps:

[0044] S1. Add fly ash treated with plasma activation, nano-scale metal oxide catalyst, metal organic framework functionalized organic ligand ZIF-8 type MOF and high-purity water in proportion to a container with a stirring device, start stirring, and control the stirring speed at 400 rpm. Add a solid suspension stabilizer during the stirring process to ensure the stability of the suspension, stir evenly until the suspension is uniform and consistent without obvious precipitation and stratification, and the stirring time is 45 minutes; filter the prepared suspension, use a filter with a pore size of 50 μm to remove possible large particle impurities, and obtain a pure suspension for standby use;

[0045] S2. Place the suspension in a high-pressure reactor and use graded temperature control. In the initial stage of the reaction, the reaction temperature is controlled at 70°C for 2 hours; then cool to 45°C and react for 2 hours; the pressure is 8MPa, and CO2 gas is introduced under ultrasonic conditions. The ultrasonic oscillation frequency is set to 30kHz to ensure that the fly ash particles in the suspension are fully in contact with CO2 to promote the mineralization reaction. The gas flow rate is controlled to 30mL / min to allow CO2 to fully react with the fly ash in the suspension and carry out the mineralization reaction for 4 hours; during the mineralization process, the pH value of the reaction environment is dynamically adjusted to 8 using an intelligent pH regulator poly(acrylic acid-co-acrylamide) copolymer (pre-prepared into an aqueous solution with a mass concentration of 8%, added before the suspension is added to the high-pressure reactor) to maximize the mineralization efficiency;

[0046] S3. Centrifuge the reaction solution obtained in step S2 at a speed of 4000 rpm for 45 minutes to separate the mineralized product from the suspension by high-speed centrifugation. Then, place the precipitate in a freeze dryer and dry it at -30°C for 18 hours to ensure that the moisture in the precipitate is completely removed. Freeze drying can effectively retain the structure and chemical properties of the product and improve the stability of the mineralized product. Finally, a stable ultrafine nano-scale carbonate solid material, i.e., a multifunctional composite material, is obtained.

[0047] The mechanical properties of the nano-scale carbonate solid material prepared in this example and ordinary building materials in terms of compressive strength and flexural strength are compared. Figure 1 As shown, from Figure 1 It can be seen that in nano-scale carbonate solid materials, the compressive strength is close to 32MPa, while the flexural strength is about 6MPa. In contrast, the compressive strength of ordinary building materials is about 15MPa, and the flexural strength is lower, only about 3.5MPa. This shows that nano-scale carbonate solid materials are significantly superior to ordinary building materials in both compressive and flexural strength, especially in compressive strength. This comparison highlights that nano-scale carbonate solid materials have higher application value in the field of construction.

[0048] The adsorption curve and desorption curve of the nano-scale carbonate solid material prepared in this example in nitrogen are as follows: Figure 2 As shown, from Figure 2 It can be seen from the figure that the adsorption amount of the adsorption curve increases rapidly at low relative pressure and then slows down, indicating that the material has many active sites on the surface. Micropores preferentially adsorb nitrogen at low pressure. When the pressure increases, the mesopores and macropores gradually participate in the adsorption and approach saturation. The desorption amount of the desorption curve decreases as the pressure decreases. The nitrogen adsorbed at high pressure is easy to desorb, while the nitrogen adsorbed at low pressure is difficult to desorb. The adsorption-desorption curves do not overlap to form a hysteresis loop, reflecting the complex pore structure of the material and the different pore size distribution. The adsorption amount of this material is as high as 270cm 3 / g, indicating that the material has strong adsorption performance. This advantage can make the material play an important role in the fields of carbon dioxide mineralization and storage.

[0049] Example 2

[0050] A multifunctional composite material for CO2 storage based on fly ash mineralization, comprising the following raw materials in parts by weight: 70 parts of fly ash treated with plasma activation, 3 parts of nano-scale metal oxide catalyst, 5 parts of metal organic framework functionalized organic ligand ZIF-8 type MOF, 1 part of intelligent pH regulator poly(acrylic acid-co-acrylamide) copolymer, 3 parts of solid suspension stabilizer, and 10 parts of high-purity water;

[0051] The fly ash treated by plasma activation contains 50wt% SiO2, 20wt% Al2O3, 15wt% CaO and 15wt% other components.

[0052] The fly ash is treated with high-temperature plasma to improve its surface activity and reactivity. During the treatment process, oxygen plasma reacts with metal oxides in the fly ash, increasing the specific surface area of ​​the fly ash, thereby improving its reactivity with CO2. The specific treatment process is as follows: collect the fly ash in a dust-free environment, screen and remove large impurities, put it into a plasma reactor, pass oxygen with an oxygen flow rate of 10L / min, and adjust the plasma generator power to 500W to ensure that the fly ash surface can fully contact the plasma; treat at 800℃ for 1h to ensure that the surface activity of the fly ash is maximized; after the treatment is completed, take out the fly ash and cool it naturally to room temperature for use.

[0053] The preparation process of the nano-scale metal oxide catalyst is as follows: calcium oxide, magnesium oxide and zinc oxide are first put into a ball mill at a molar ratio of 1:0.5:0.3, mixed and ball-milled for 2 hours to obtain a mixed powder, the mixed powder is calcined at 800° C. for 2 hours under nitrogen protection to obtain a composite oxide, the composite oxide is naturally cooled to room temperature, and then placed in a graphene dispersion liquid with a concentration of 5 mg / mL, ultrasonically dispersed for 1 hour to uniformly coat the graphene on the surface of the composite oxide, and uncoated graphene is separated by centrifugation to obtain a nano-scale metal oxide catalyst;

[0054] The preparation process of the metal organic framework functionalized organic ligand ZIF-8 type MOF is as follows: accurately weigh zinc nitrate as a metal salt and 2-methylimidazole as an organic ligand and put them into a reaction bottle, the molar ratio between zinc ion and 2-methylimidazole is 1:2, add deionized water to adjust the pH to 3, perform a hydrothermal synthesis reaction at 80° C. in a constant temperature water bath for 12 hours, naturally snap-cool after the reaction is completed, centrifuge to obtain a MOF material, wash the MOF material with anhydrous ethanol for 3 times, and vacuum dry it at 60° C. for 12 hours;

[0055] The mass ratio of acrylic acid to acrylamide in the poly(acrylic acid-co-acrylamide) copolymer of the smart pH regulator is 1:0.8, and the molecular weight of the poly(acrylic acid-co-acrylamide) copolymer is 50,000;

[0056] The solid suspension stabilizer is modified polyvinyl pyrrolidone. The modification process of the modified polyvinyl pyrrolidone is as follows: divinyl benzene is used as a crosslinking agent, and a chemical crosslinking reaction occurs with polyvinyl pyrrolidone under the action of an initiator, and the crosslinking degree is controlled at 5%.

[0057] The preparation method of the above-mentioned multifunctional composite material for CO2 storage based on fly ash mineralization comprises the following steps:

[0058] S1. Add fly ash treated with plasma activation, nano-scale metal oxide catalyst, metal organic framework functionalized organic ligand ZIF-8 type MOF and high-purity water in proportion to a container with a stirring device, start stirring, add a solid suspension stabilizer during stirring to ensure the stability of the suspension, stir evenly until the suspension is uniform and consistent without obvious precipitation and stratification, and the stirring time is 30 minutes; filter the prepared snapshot suspension to remove possible large particle impurities to obtain a pure suspension for standby use;

[0059] S2. Place the suspension in a high-pressure reactor and use graded temperature control. In the initial stage of the reaction, the reaction temperature is controlled to 60°C for 1 hour; then cool to 40°C and react for 1 hour; the pressure is 5MPa, and CO2 gas is introduced under ultrasonic conditions. The ultrasonic oscillation frequency is set to 20kHz to ensure that the fly ash particles in the suspension are fully in contact with CO2 to promote the mineralization reaction. The gas flow rate is controlled to 10mL / min to allow CO2 to fully react with the fly ash in the suspension and carry out the mineralization reaction for 2 hours; during the mineralization process, the pH value of the reaction environment is dynamically adjusted to 7 using the intelligent pH regulator poly(acrylic acid-co-acrylamide) copolymer to maximize the mineralization efficiency;

[0060] S3. Centrifuge the reaction solution obtained in step S2 at a speed of 3000 rpm for 30 minutes to separate the mineralized product from the suspension by high-speed centrifugation. Then, place the precipitate in a freeze dryer and dry it at -40°C for 12 hours to ensure that the water in the precipitate is completely removed. Freeze drying can effectively retain the structure and chemical properties of the product and improve the stability of the mineralized product. Finally, a stable ultrafine nano-scale carbonate solid material, i.e., a multifunctional composite material, is obtained.

[0061] The composite material prepared in this embodiment is experimentally confirmed to be significantly superior to ordinary building materials in terms of compressive strength and flexural strength, and especially shows a huge advantage in compressive strength. This shows that the composite material prepared in the present invention has a higher application value in the field of construction.

[0062] In addition, the composite material prepared in this example was subjected to adsorption and desorption experiments. The experimental process was consistent with that in the example, and the experimental results were similar to those in Example 1. The adsorption capacity of the material was as high as 260 cm 3 / g, indicating that the material has strong adsorption performance. This advantage can make the material play an important role in the fields of carbon dioxide mineralization and storage.

[0063] Example 3

[0064] A multifunctional composite material for CO2 storage based on fly ash mineralization, comprising the following raw materials in parts by weight: 85 parts of fly ash treated with plasma activation, 7 parts of nano-scale metal oxide catalyst, 10 parts of metal organic framework functionalized organic ligand ZIF-8 type MOF, 2 parts of intelligent pH regulator poly(acrylic acid-co-acrylamide) copolymer, 5 parts of solid suspension stabilizer, and 20 parts of high-purity water;

[0065] The fly ash treated by plasma activation contains 65wt% SiO2, 20wt% Al2O3, 5wt% CaO and 10wt% other components;

[0066] The fly ash is treated with high-temperature plasma to improve its surface activity and reactivity. During the treatment process, oxygen plasma reacts with metal oxides in the fly ash, increasing the specific surface area of ​​the fly ash, thereby improving its reactivity with CO2. The specific treatment process is as follows: collect the fly ash in a dust-free environment, screen and remove large impurities, put it into a plasma reactor, pass oxygen, and adjust the plasma generator power to 1500W to ensure that the fly ash surface can fully contact the plasma; treat at 1200℃ for 2h to ensure the maximum surface activity of the fly ash; after the treatment is completed, take out the fly ash and cool it naturally to room temperature for use.

[0067] The preparation process of the nano-scale metal oxide catalyst is as follows: calcium oxide, magnesium oxide and zinc oxide are first put into a ball mill at a molar ratio of 1:1.5:1, mixed and ball-milled for 4 hours to obtain a mixed powder, the mixed powder is calcined at 900° C. for 4 hours under nitrogen protection to obtain a composite oxide, the composite oxide is naturally cooled to room temperature, and then placed in a graphene dispersion liquid with a concentration of 15 mg / mL, ultrasonically dispersed for 3 hours to uniformly coat the graphene on the surface of the composite oxide, and uncoated graphene is separated by centrifugation to obtain a nano-scale metal oxide catalyst;

[0068] The preparation process of the metal organic framework functionalized organic ligand ZIF-8 type MOF is as follows: accurately weigh zinc nitrate as a metal salt and 2-methylimidazole as an organic ligand and put them into a reaction bottle, so that the molar ratio between zinc ions and 2-methylimidazole is 1:2, add deionized water to adjust the pH to 6, perform a hydrothermal synthesis reaction at 120° C. in a constant temperature water bath for 48 hours, cool naturally after the reaction, centrifuge to obtain a MOF material, wash the MOF material with anhydrous ethanol for 5 times, and vacuum dry it at 80° C. for 24 hours;

[0069] The mass ratio between acrylic acid and acrylamide in the poly(acrylic acid-co-acrylamide) copolymer of the smart pH regulator is 1:1.2, and the molecular weight of the poly(acrylic acid-co-acrylamide) copolymer is 100,000;

[0070] The solid suspension stabilizer is modified polyvinyl pyrrolidone. The modification process of the modified polyvinyl pyrrolidone is as follows: divinyl benzene is used as a crosslinking agent, and a chemical crosslinking reaction occurs with polyvinyl pyrrolidone under the action of an initiator, and the crosslinking degree is controlled at 15%.

[0071] The preparation method of the above-mentioned multifunctional composite material for CO2 storage based on fly ash mineralization comprises the following steps:

[0072] S1. Add fly ash treated with plasma activation, nano-scale metal oxide catalyst, metal organic framework functionalized organic ligand ZIF-8 type MOF and high-purity water in proportion to a container with a stirring device, start stirring, add a solid suspension stabilizer during stirring to ensure the stability of the suspension, stir evenly until the suspension is uniform and consistent without obvious precipitation and stratification, and the stirring time is 60 minutes; filter the prepared suspension to remove possible large particle impurities to obtain a pure suspension for standby use;

[0073] S2. Place the suspension in a high-pressure reactor and use graded temperature control. In the initial stage of the reaction, the reaction temperature is controlled to 80°C for 3 hours; then cool to 50°C and react for 3 hours; the pressure is 10MPa, and CO2 gas is introduced under ultrasonic conditions. The ultrasonic oscillation frequency is set to 40kHz to ensure that the fly ash particles in the suspension are fully in contact with CO2 to promote the mineralization reaction. The gas flow rate is controlled to 50mL / min to allow CO2 to fully react with the fly ash in the suspension. The mineralization reaction is carried out for 6 hours; during the mineralization process, the pH value of the reaction environment is dynamically adjusted to 9 using the intelligent pH regulator poly(acrylic acid-co-acrylamide) copolymer to maximize the mineralization efficiency;

[0074] S3. Centrifuge the reaction solution obtained in step S2 at a speed of 5000 rpm for 60 minutes to separate the mineralized product from the suspension by high-speed centrifugation. Then, place the precipitate in a freeze dryer and dry it at -20°C for 24 hours to ensure that the water in the precipitate is completely removed. Freeze drying can effectively retain the structure and chemical properties of the product and improve the stability of the mineralized product. Finally, a stable ultrafine nano-scale carbonate solid material, i.e., a multifunctional composite material, is obtained.

[0075] The composite material prepared in this embodiment is experimentally confirmed to be significantly superior to ordinary building materials in terms of compressive strength and flexural strength, and especially shows a huge advantage in compressive strength. This shows that the composite material prepared in the present invention has a higher application value in the field of construction.

[0076] In addition, the composite material prepared in this example was subjected to adsorption and desorption experiments. The experimental process was consistent with that in the example, and the experimental results were similar to those in Example 1. The adsorption capacity of the material was as high as 280 cm 3 / g, indicating that the material has strong adsorption performance. This advantage can make the material play an important role in the fields of carbon dioxide mineralization and storage.

Claims

1. A multifunctional composite material for CO2 storage based on fly ash mineralization, characterized in that: The method is composed of the following raw materials in parts by weight: 70-85 parts of fly ash treated by plasma activation, 3-7 parts of nano-scale metal oxide catalyst, 5-10 parts of metal organic framework functionalized organic ligand ZIF-8 type MOF, 1-2 parts of smart pH regulator poly(acrylic acid-co-acrylamide) copolymer, 3-5 parts of solid suspension stabilizer, and 10-20 parts of high-purity water; The fly ash treated by plasma activation contains 50-65wt% SiO2, 20-30wt% Al2O3, 5-15wt% CaO, and the remaining components are inevitable impurities; The preparation process of the nano-scale metal oxide catalyst is as follows: calcium oxide, magnesium oxide and zinc oxide are weighed in order according to the ratio, ball-milled and mixed to obtain a mixed powder, calcined at high temperature to form a composite oxide, and then the composite oxide is placed in a graphene dispersion liquid, ultrasonically dispersed, and the graphene is uniformly coated on the surface of the composite oxide to obtain the nano-scale metal oxide catalyst; The solid suspension stabilizer is polyvinyl alcohol or modified polyvinyl pyrrolidone.

2. The multifunctional composite material for CO2 storage based on fly ash mineralization according to claim 1, characterized in that: The treatment process of the fly ash treated by plasma activation is as follows: the fly ash is collected in a dust-free environment, sieved to remove large impurities, placed in a plasma reactor, oxygen is introduced, the oxygen flow rate is 10-50L / min, the plasma generator power is adjusted to 500-1500W, treated at 800-1200°C for 1-2h, and naturally cooled to room temperature.

3. A multifunctional composite material for CO2 storage based on fly ash mineralization according to claim 1 or 2, characterized in that: The preparation process of the metal organic framework functionalized organic ligand ZIF-8 type MOF is as follows: accurately weigh zinc nitrate as a metal salt and 2-methylimidazole as an organic ligand and put them into a reaction bottle, the molar ratio between zinc ions and 2-methylimidazole is 1:2, deionized water is added to adjust the pH to 3-6, a hydrothermal synthesis reaction is carried out in a constant temperature water bath at 80-120° C. for 12-48 hours, the reaction is naturally cooled after completion, and a MOF material is obtained by centrifugation, and the MOF material is washed with anhydrous ethanol for 3-5 times and vacuum dried at 60-80° C. for 12-24 hours.

4. A multifunctional composite material for CO2 storage based on fly ash mineralization according to claim 1 or 2, characterized in that: The molar ratio of calcium oxide, magnesium oxide and zinc oxide is 1: (0.5-1.5): (0.3-1); ball milling mixing is 2-4 hours; calcination temperature is 800-900° C., and calcination time is 2-4 hours; ultrasonic dispersion is 1-3 hours; and the concentration of graphene dispersion is 5-15 mg / mL.

5. A multifunctional composite material for CO2 storage based on fly ash mineralization according to claim 1 or 2, characterized in that: The mass ratio of acrylic acid to acrylamide in the poly(acrylic acid-co-acrylamide) copolymer is 1:(0.8-1.2), and the molecular weight of the poly(acrylic acid-co-acrylamide) copolymer is 50,000-100,000.

6. A multifunctional composite material for CO2 storage based on fly ash mineralization according to claim 1 or 2, characterized in that: The molecular weight of the polyvinyl alcohol is 100,000-300,000. The modification process of the modified polyvinyl pyrrolidone is as follows: divinyl benzene is used as a crosslinking agent, and a chemical crosslinking reaction occurs with polyvinyl pyrrolidone under the action of an initiator, and the crosslinking degree is controlled at 5%-15%.

7. A method for preparing a multifunctional composite material based on fly ash mineralization and CO2 storage as claimed in claim 1, characterized in that: The steps include: S1. Mix fly ash treated with plasma activation, nano-scale metal oxide catalyst, metal organic framework functionalized organic ligand ZIF-8 type MOF and high-purity water in proportion, add solid suspension stabilizer during stirring, stir evenly to form a suspension, and stir for 30-60 minutes; S2. Place the suspension in a high-pressure reactor, control the reaction temperature to 40-80°C and the pressure to 5-10MPa, introduce CO2 gas under ultrasonic conditions, and carry out mineralization reaction for 2-6 hours; during the mineralization process, use the intelligent pH regulator poly(acrylic acid-co-acrylamide) copolymer to dynamically control the pH value of the reaction environment to 7-9; S3. Centrifuge the reaction solution obtained in step S2 at a speed of 3000-5000 rpm for 30-60 min to separate the mineralized product from the suspension by high-speed centrifugation, and then place the precipitate in a freeze dryer and dry it at -40°C to -20°C for 12-24h to obtain an ultrafine nano-scale carbonate solid material, i.e., a multifunctional composite material.

8. The method for preparing a multifunctional composite material for CO2 storage based on fly ash mineralization according to claim 7, characterized in that: In step S2, graded temperature control is adopted, and the reaction temperature is controlled at 60-80°C in the initial stage of the reaction, and the reaction is carried out for 1-3 hours; then the temperature is lowered to 40-50°C and the reaction is carried out for 1-3 hours.

9. The method for preparing a multifunctional composite material for CO2 storage based on fly ash mineralization according to claim 7 or 8, characterized in that: In step S2, a poly(acrylic acid-co-acrylamide) copolymer aqueous solution with a mass concentration of 5%-10% is prepared in advance as an intelligent pH regulator, and the intelligent pH regulator is added before the suspension is added to the high-pressure reactor.

10. The method for preparing a multifunctional composite material for CO2 storage based on fly ash mineralization according to claim 7 or 8, characterized in that: In step S2, the ultrasonic oscillation frequency is 20-40kHz; the CO2 gas flow rate is 10-50mL / min.

Citation Information

Patent Citations

  • Preparation method of Cu-MOF-Fe fly ash catalyst for denitration and demercuration

    CN111701622A

  • Preparation method and application of fly ash CO2 trapping agent

    CN112707746A

  • ZIF-8 / rGO composite photocatalyst as well as preparation method and application thereof

    CN116078437A

  • Coal chemical industry solid waste mineralization utilization method and application thereof

    CN116493397A

  • Carbon dioxide trapping material based on waste PET metal organic framework material compounded with fly ash and preparation method of carbon dioxide trapping material

    CN116571220A

Cited By

  • Mining cemented filling mortar material for mineralizing and sealing CO2 and preparation method thereof

    CN120004565A

  • Mine carbon dioxide adsorption, storage and flame retardant method

    CN120402176A

  • Method for preparing fireproof coating from fly ash waste and application of fireproof coating

    CN121006124A

  • Modified ultrafine fly ash, UHPC, preparation method and application

    CN121717568A